2004
DOI: 10.1038/sj.bjc.6602201
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial CD8+ T-cell-count becomes a prognostic factor after a longer follow-up period in human colorectal carcinoma: possible association with suppression of micrometastasis

Abstract: T-cell infiltration into human cancer tissues can be a manifestation of host immune responses to cancer cells. The present study was undertaken to explore the clinicopathological significance of intraepithelial CD8 þ T cells using 371 consecutively sampled human colorectal carcinomas. By univariate analysis, we noted that the survival curves by intraepithelial CD8 þ T cells became separated only after 1 to 2 years postoperation. Multivariate analyses revealed that the beneficial effect of this factor becomes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
152
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(167 citation statements)
references
References 16 publications
(16 reference statements)
12
152
1
1
Order By: Relevance
“…48 The prognostic value of lymphocytes does not appear to be reflected at the systemic level, however, as whilst the number of tumourinfiltrating CD8+ T-lymphocytes was found to correlate with patient outcome in primary CRC, the number of these cells in the systemic circulation showed no correlation with prognosis. 49,50 Similarly, a recent study found no correlation between total circulating lymphocyte count and outcome in patients with either operable primary CRC or unresectable CLM. 23 The findings of the current study are in line with these data.…”
Section: Discussionmentioning
confidence: 97%
“…48 The prognostic value of lymphocytes does not appear to be reflected at the systemic level, however, as whilst the number of tumourinfiltrating CD8+ T-lymphocytes was found to correlate with patient outcome in primary CRC, the number of these cells in the systemic circulation showed no correlation with prognosis. 49,50 Similarly, a recent study found no correlation between total circulating lymphocyte count and outcome in patients with either operable primary CRC or unresectable CLM. 23 The findings of the current study are in line with these data.…”
Section: Discussionmentioning
confidence: 97%
“…31 observed that the presence of intratumoral CD8 1 T cells in cervical cancer was correlated with the lack of pelvic lymph node spread and was, therefore, correlated indirectly with prognosis. A high number of tumor-infiltrating CD8 1 T lymphocytes were observed as a favorable prognostic factor for survival in some studies of human cancers, including endometrial cancer, 32 ovarian cancer, 8 colorectal cancer, 33 esophageal cancer 34 and urothelial carcinoma. 35 Other studies on non-small cell lung cancer, 36 anal squamous cell carcinoma 24 and renal cell carcinoma 37 reported that CD8 1 T lymphocytes were a negative prognostic factor.…”
Section: Comparative Numbers Of Cd4mentioning
confidence: 99%
“…It has been postulated that MSI-H CRC are more immunogenic than microsatellite stable (MSS) tumors because of the generation of a large number of abnormal peptides by frameshift mutations [49,[65][66][67][68][69][70]. However, in the analysis of Chiba et al [52] there was no significant increase in the number of CD8 + IEL in cases with MSI. Therefore, it appears that although MSI could be associated with a high infiltration of T cells in tumor tissue, additional mechanisms like cross-priming of antigen-presenting cells by released intracellular antigens or the use of HLA class II machinery and T helper cell activity may provide an alternative pathway for immune stimulation in vivo [41,65,67].…”
Section: Tumor-infiltrating Lymphocytes and Msi-statusmentioning
confidence: 99%
“…However, while TILs might be expected to explain the increased apoptotic rate and improved prognosis of MSI-H cancers, it is likely that MSI-H cancers are intrinsically more prone to apoptosis, independently of T cell attack [73]. In addition, Buckowitz et al [74] and Chiba et al [52] suggested a protective role of functionally active lymphocytes directed against MSI-H CRCs, which may prevent tumor cell dissemination and metastasis formation in distant organs. Furthermore, it has been postulated that the abundance of CD8 + TILs found in MSI-H CRC might be due to the failure of these tumor cells to upregulateFasL.…”
Section: Role In Prognosismentioning
confidence: 99%